Pls answer????????????
Attachments:
![](https://hi-static.z-dn.net/files/d87/34785005f40a879dad27b22501d55bbb.png)
Answers
Answered by
3
Here is your answer :-
take the steps in consideration ;-
P ( x ) = x³ + 8x² + 17x + ax
divide by ( x + 2 )
on putting the value of x we get
-2³ + 8 × 4 + 17×-2 + -2a = 0
-8 + 32 + -34 - 2a = 0
-10 -2a = 0
a = -5
now , when p( x ) divide by x + 1
on putting the value we get :-
-1³ + 8 -17 -a = 0
- a -10 = 0
a = 10
hope it help you !!!
thanks !!
take the steps in consideration ;-
P ( x ) = x³ + 8x² + 17x + ax
divide by ( x + 2 )
on putting the value of x we get
-2³ + 8 × 4 + 17×-2 + -2a = 0
-8 + 32 + -34 - 2a = 0
-10 -2a = 0
a = -5
now , when p( x ) divide by x + 1
on putting the value we get :-
-1³ + 8 -17 -a = 0
- a -10 = 0
a = 10
hope it help you !!!
thanks !!
Similar questions